MEDIA SPACE AS AN IMPORTANT FACTOR IN BUILDING THE INFORMATION SOCIETY - Holovanova N.V. (Pressing Problems of Public Administration, 2017)
Different approaches and systems of approaches to the de nition of “media space” are studied.Nature of processes in media space, features such as media space and media space in its relationshipwith the social space are re ned. Different models of global society are considered. Quantitativemeasures implementing ICT in Ukraine in 2011–2016 are resulted, an assessment of government’sinformation policy is made. The model of the modern media space in the context of globalization andtime is improved.